2006
DOI: 10.1017/s0317167100005370
|View full text |Cite
|
Sign up to set email alerts
|

West Nile Virus Encephalomyelitis with Polio-like Paralysis & Nigral Degeneration

Abstract: West Nile virus (WNV) is a mosquito-borne RNA virus in the genus Flavivirus (family Flaviviridae), and a member of the Japanese encephalitis serological group which comprises eight virus species including Japanese encephalitis virus (JEV) and St. Louis encephalitis virus (SLEV), and two subtype viruses. 1 Although most cases of WNV infection are subclinical or result in a mild, self-limited febrile illness known as West Nile fever, a minority of patients (<1%) develop acute neurologic disease, which can be sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 23 publications
1
19
0
Order By: Relevance
“…These lesions are particularly notable on T2‐ and fluid attenuation inversion recovery (FLAIR) sequences (8, 49, 50). The location of these MRI abnormalities corresponds to regions of the CNS with prominent inflammation on histology and virus localization by IHC of reported cases of neuro‐invasive WNV disease (1, 3, 5–7, 9, 10, 12, 13, 15, 19–21, 25, 26, 28, 37, 40, 44–48, 52, 53), as confirmed in this series.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…These lesions are particularly notable on T2‐ and fluid attenuation inversion recovery (FLAIR) sequences (8, 49, 50). The location of these MRI abnormalities corresponds to regions of the CNS with prominent inflammation on histology and virus localization by IHC of reported cases of neuro‐invasive WNV disease (1, 3, 5–7, 9, 10, 12, 13, 15, 19–21, 25, 26, 28, 37, 40, 44–48, 52, 53), as confirmed in this series.…”
Section: Discussionsupporting
confidence: 78%
“…Histopathologic examination of central nervous system (CNS) tissues from patients with WNV neuro‐invasive disease shows perivascular inflammation, microglial nodules, neuronophagia, and variable necrosis and neuronal loss, with pathologic changes concentrated in the brainstem, deep gray nuclei and anterior horns of the spinal cells (1, 3, 5–7, 9, 10, 12, 13, 15, 19–21, 25, 26, 28, 37, 40, 44–48, 52, 53). Spinal cord inflammation was seen in 17 of 23 patients who died with WNV neuro‐invasive disease (15).…”
Section: Introductionmentioning
confidence: 99%
“…Although several studies have reported extensive pathological changes in the substantia nigra in patients with neuroinvasive WNV infections, not all of the patients with abnormalities in the substantia nigra were reported to have parkinsonian signs. For instance, Bosanko and colleagues described a patient with severe‐involvement substantia nigra (patchy marked loss of neurons and pigment incontinence in the pars compacta) that correlated with presence of parkinsonian symptoms, whereas 1 of the cases described by Schafernak and Bigio did not have parkinsonism even though autopsy revealed multifocal necrosis and macrophage influx in the substantia nigra and red nuclei. This differential outcome of WNV infection in the background of substantia nigra involvement raises the question of why all the patients with substantia nigra involvement do not develop parkinsonism, and it underscores the requirement of additional autopsy‐based studies to understand this complex phenomenon.…”
Section: Resultsmentioning
confidence: 99%
“…Histological findings in West Nile neuroinvasive disease are nonspecific and typical of many viral encephalitides, and these are characterized by perivascular lymphocytic infiltrates, microglial nodules, neuronal loss, and neuronophagia [67,[70][71][72]. In severe cases, necrosis can be seen [73]. Most commonly affected regions of the central nervous system (CNS) have extrapyramidal (movement-related) function and include the brainstem (medulla and pons), deep gray matter nuclei (substantia nigra of the basal ganglia and thalamus), and cerebellum with gray matter being the most severely affected [70,[73][74][75][76].…”
Section: Humansmentioning
confidence: 99%
“…In severe cases, necrosis can be seen [73]. Most commonly affected regions of the central nervous system (CNS) have extrapyramidal (movement-related) function and include the brainstem (medulla and pons), deep gray matter nuclei (substantia nigra of the basal ganglia and thalamus), and cerebellum with gray matter being the most severely affected [70,[73][74][75][76]. In the spinal cord, the anterior horns (ventral horns) and anterior spinal nerve roots are frequently involved and associated lower motor neuron loss results in muscle weakness [71,74,75,77,78].…”
Section: Humansmentioning
confidence: 99%